DETERMINANTS OF HUMAN RESOURCE MANAGEMENT (HRM) ADOPTION AMONG SMALL AND MEDIUM SCALE ENTERPRISES (SMEs) IN KADUNA STATE, NIGERIA - Helen Afang Andow (Malete Journal of Accounting and Finance)
The contributions of small-scale businesses to economic development are generally acknowledged. Entrepreneurs in this sector face many challenges that limit their long-term survival and development. These challenges have been linked to some economic variables such as lack of finance, inadequate infrastructure, low industrialization capacity, inconsistent government policies and poor management practices among others which interact with the economic variables to undermine the capacity of SMEs. This study examines the factors that affect the adoption of Human Resource Management Practices (HRMP) among SMEs in Kaduna state, Nigeria. The study adopted survey research design and data was gathered from purposively selected 100 SMEs respondents through copies of structured questionnaires in selected local government areas of the state. Multiple Regression Analysis was used to analyze the data obtained. Findings of the study indicated that HRM practices have significant effect on business performance at 1% level of significance. The investigation likewise uncovered that while remuneration and performance evaluation autonomously and collectively impacted on business performance, the impact of recruitment was significant. Training had an inverse relationship with business performance. The study likewise found that financial resources and firm size were main factors that had significant impact on HRM Practices adopted by SMEs in the study sample. The study recommends that an enabling environment that will encourage the adoption of HRM practices by SMEs should be provided. This is expected to facilitate their ability to grow and build up the required capacity for the promotion of sustainable development in the nation.